PENGEMBANGAN DESA WISATA ERAMAYA KABUPATEN TEMANGGUNG STUDI KERJASAMA PEMERINTAH & MASYARAKAT - Setiyo Utomo .; Fitriyah . .; Lusia Astrika . (Journal of Politic and Government Studies, 2017)
ERAMAYA TOURISM VILLAGE DEVELOPMENT INTEMANGGUNG REGENCYA JOINT STUDY BETWEEN GOVERNMENT & COMMUNITYSETIYO UTOMO(POLITICAL AND GOVERNMENT DEPARTMENT OF SOCIAL ANDPOLITICAL SCIENCE FACULTY, DIPONEGORO UNIVERSITY,SEMARANG)ABSTRACTOne of the touristic village in the district of Temanggung is Eramaya. Thevillage has some attractions for tourists to visit and this place is one of the existenceof an artificial reservoir named Embug Abhimanyu. Infrastructure tourism villageEramaya is still lacking such as access roads and the other public facilities are notequal.This type of this research is qualitative descriptive, which is intended toprovide a systematic description of the object studied. Source of data derived fromprimary data and secondary data. Determination of informants by using purposivesampling that peoples involved in the tourist village development. The collection ofdata, researchers use two (2) methods, the method are interview and literature study.The results showed that the government already has several programs todevelop Eramaya touristic village. The program is included to increase the quality ofHuman Resources (HR) Group of the tourism awareness Eramaya. Constraints facedby the government is the availability of a budget that is owned by the government aswell as the quality of community resources is still low.In implementing the program the government will work with thecommunity through a conscious group Eramaya travel. Government continues toattempt to hold the third person in the development of rural tourism however untilnow there is no private sector can join.Advice to the government is doing capital assistance in the improvement offacilities and infrastructure.Keywords: Tourism Village, Village Tourism Development, Partnership